2022
DOI: 10.3390/children9101528
|View full text |Cite
|
Sign up to set email alerts
|

ADHD-Gaming Disorder Comorbidity in Children and Adolescents: A Narrative Review

Abstract: Attention Deficit/Hyperactivity Disorder (ADHD) is a neurobiological condition characterized by developmentally inadequate levels of inattention, hyperactivity, and impulsivity, and a neurobiological disruption in brain neurotransmitters and circuitry causing abnormal responses to rewards. Playing electronic games generates a biological response that activates the neuronal circuits linked to pleasure and reward, and there is a growing attention to this type of activity, which can also turn into a mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 107 publications
0
3
0
3
Order By: Relevance
“…Second, not only patients with DSWPD but also those with GD are often complicated by neurodevelopmental disorders. Several studies have indicated that patients with GD are frequently complicated by either ADHD (142) or ASD (143). In such cases, treatment approach focusing on neurodevelopmental disorders should be included.…”
Section: Gaming Disorder and Dswpdmentioning
confidence: 99%
“…Second, not only patients with DSWPD but also those with GD are often complicated by neurodevelopmental disorders. Several studies have indicated that patients with GD are frequently complicated by either ADHD (142) or ASD (143). In such cases, treatment approach focusing on neurodevelopmental disorders should be included.…”
Section: Gaming Disorder and Dswpdmentioning
confidence: 99%
“…Sabe-se que, segundo Salerno et al, (2022) no TDAH ocorrem déficits no sistema de recompensa, envolvendo o córtex cingulado anterior, córtex pré-frontal e orbitofrontal. A principal região afetada mostrou-se ser o córtex cingulado anterior, que é responsável pela modulação da atividade neuronal da rede de controle executivo, participando, assim, da tomada de decisões relativas ao sistema de recompensa, regulação das emoções e do sistema de recompensa.…”
Section: Fisiopatologia De Potenciais Prejuízos Neurológicosunclassified
“…Concomitantemente, outro estudo investigou a relação do TDAH ao vício em jogos digitais, e relacionou redução da conectividade funcional cerebral entre o córtex frontal e o subcorticóide, concluindo que ambos possuíam redução da funcionalidade cerebral do giro frontal médio direito para o caudado, e do cingulado esquerdo para o caudado em relação aos pacientes normais (Salerno et al, 2022).…”
Section: Fisiopatologia De Potenciais Prejuízos Neurológicosunclassified
See 1 more Smart Citation
“…Salerno and colleagues [4] examined the state of the art related to the comorbidity between Attention Deficit Hyperactivity Disorder (ADHD) and Gaming Disorder (GD). Authors findings not only confirmed the frequent co-occurrence of ADHD and GD, but also that ADHD is associated with poor GD clinical outcomes, leading authors to state that gaming in children and adolescents with ADHD constitutes a pathological complication and not a functional coping strategy.…”
mentioning
confidence: 99%